FDI, Market Structure and R&D Investments in China - Nannan Lundin; Ping He; Jinchang Qian; Fredrik Sjöholm (Research Institute of Industrial Economics (IFN), 2007)
FDI can be an important channel for developing countries ability to get access to new technology. The impact of FDI on domestically-owned firms technology development is less examined but it is frequently argued that technology externalities or demonstration effects could have a positive impact. Another and so far little examined effect of FDI on technology development in domestically-owned firms is through the impact on competition. We examine the effect of FDI on competition in the Chinese manufacturing sector and the effect of competition on firms R&D. Our analysis is conducted on a large dataset including all Chinese large and medium sized firms over the period 1998-2004. Our results show that FDI increases competition but there are no strong indications of competition affecting investments in R&D.
Keywords: F23; L11; O31; 330; China; FDI; Competition; R&D; Direktinvestition; Wettbewerb; Betriebliche Forschung; Verarbeitendes Gewerbe; China